THE HISTORY AND DYNAMIC OF CUSTOMARY LAND TENURE IN THE VILLAGE OF PROBUR UTARA HABOLLAT, ALOR DISTRICT - Sudiyono, Sudiyono (P2KK LIPI, 2015)
This article aims to describe the history as well as the dynamics of customary land tenure in Probur Utara Habollat Village Alor District. There are six factors influencing the dynamics of customary land tenure, namely: (1) The expansion of village administration area as a consequence of the rising demand on public services; (2) The rising of the village infrastructure development, that needs legal formal regulation on land; (3) The customary land tenure, which is closely related with the local system believe, in the recent days have changed along with the process of Islamization and Christianization; (4) The implementation of community forestry programme under government’s control that has weakened the authority of traditional leaders in the land use management; (5) The land titling policy from the local government of Alor District that has shifted the land rights from the community rights to the personal rights; and (6) The very weak social economic life of the Beilel as a minority tribal group. Keywords: dynamic, customary land tenure, Probur Utara Habollat Village